Disease, climate, environment and the fortunes of Buddhism during the Tibetan Empire 618–842 CE - Zou, Yi; Cheng, Jianquan; Cresswell, Mark P.; Lageard, Jonathan G. A. (ERDKUNDE, 2024)
The official adoption of Buddhism by the Tibetan state in the mid-8th Century (761-762 CE) was relatively late compared to its permeation from northern India to elsewhere in south and east Asia, due to the country’s geographical isolation. Whilst reasons for its adoption remain uncertain, it is thought that the religion provided a strong unifying influence permitting both the consolidation and subsequent expansion of the Tibetan Empire. Early historical records suggest that the religion was prohibited in 739-741 CE and again in 841-842 CE, the latter coinciding with the fall of the Tibetan Empire. This research presents a detailed examination of Tibetan and Chinese historical records and also of recent fine-resolution palaeoclimatic reconstructions to demonstrate that the ‘oscillating fate’ of Buddhism during the Tibetan Empire (618-842 CE), was not only linked to the economic fortunes of the Tibetan state as previously envisaged, but also inextricably to disease, the long-term regional climatic deterioration and possibly also to a series of natural disasters, many of which were recorded in the north and north-west of the Tang Empire adjacent to Tibet, as well as in Tibet itself. These ‘disasters’ noted in the historic records, and both catalogued and quantified here, indicate extreme pressures placed on the rural economy of the Tibetan Plateau and adjoining areas by crop failures, the death of many livestock and associated widespread famine and human mortality. The ‘chaos & disorder’ of the latter stages of the reign of Emperor Ralpachen (815-836/838 CE), as well as the Second Prohibition of Buddhism by the last Tibetan Emperor Lang Darma can therefore now not only be related to climatic-environmental deterioration, but also to the likely loss of public faith in both Tibetan Emperors and in Buddhism. It is possible that in the eyes of superstitious Tibetans, neither their rulers nor the state religion could address an accelerating spiral of crises. Devine displeasure could have been further signified by a devastating earthquake in Tibet sometime between 839-842 CE and the subsequent ‘implosion’ of the Tibetan Empire should no longer be considered surprising.